2002
DOI: 10.7326/0003-4819-137-11-200212030-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subclinical Thyroid Dysfunction on the Heart

Abstract: The heart responds to the minimal but persistent changes in circulating thyroid hormone levels typical of subclinical thyroid dysfunction. Thus, the condition is not a compensated biochemical change sensu strictu, and timely treatment should be considered in an attempt to avoid adverse cardiovascular effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
242
3
17

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 386 publications
(275 citation statements)
references
References 99 publications
13
242
3
17
Order By: Relevance
“…Both subclinical and overt hypothyroidism have been associated with normal/ depressed systolic function, left ventricular diastolic dysfunction at rest, systolic and diastolic dysfunction during effort, increased peripheral vascular resistance, and impaired endothelial function (18,19). The similar pattern of these cardiovascular abnormalities in subclinical and overt hypothyroidism suggests that there is a continuum in cardiovascular effects related to thyroid hormone deficiency and also that a lesser degree of thyroid hormone deficiency may induce severe cardiovascular abnormalities.…”
Section: Cardiovascular Effects Of Short-term Hypothyroidismmentioning
confidence: 76%
“…Both subclinical and overt hypothyroidism have been associated with normal/ depressed systolic function, left ventricular diastolic dysfunction at rest, systolic and diastolic dysfunction during effort, increased peripheral vascular resistance, and impaired endothelial function (18,19). The similar pattern of these cardiovascular abnormalities in subclinical and overt hypothyroidism suggests that there is a continuum in cardiovascular effects related to thyroid hormone deficiency and also that a lesser degree of thyroid hormone deficiency may induce severe cardiovascular abnormalities.…”
Section: Cardiovascular Effects Of Short-term Hypothyroidismmentioning
confidence: 76%
“…Persistent subclinical hyperthyroidism by TSH-suppressive doses of levothyroxine has been shown to affect heart morphology and function in different groups of patients. Biondi et al showed that subclinical hyperthyroidism is associated with increased heart rate, atrial arrhythmias, increased left ventricular mass with marginal concentric remodeling, impaired ventricular relaxation, reduced exercise performance and increased risk for cardiovascular death [17]. Another study by Donatelli et al, on women with overt and subclinical hyperthyroidism, indicated a global impairment of diastolic heart performance, complicated in overt hyperthyroidism by left ventricular concentric hypertrophy [18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 'subclinical' hyperthyroidism reduces the quality of life, affecting both the psycho and somatic components of wellbeing, and produces relevant signs and symptoms of excessive thyroid hormone action, often mimicking adrenergic overdrive. 'Subclinical' hyperthyroidism exerts many relevant effects on the cardiovascular system (113). It is usually associated with a higher heart rate and a higher risk of supraventricular arrhythmias, and with an increased left ventricular mass, often accompanied by impaired diastolic function and, sometimes, by reduced systolic performance on effort and decreased exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%